(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2014)
يهدفُ هذا البحث إلى التعرّف على شاعرٍ عاشَ العصرَ الأمويَّ، في كنفِ أسرةٍ موفورةِ المالِ،ومقرَّبةٍ من البلاطِ الأمويِّ، وفي تحديدِ الهدفِ؛ يحاولُ البحثُ تحليلَ النّصّ الشّعريّ لديه وتسليطَ الضّوءِ على أبرزِ ملامحِ إبداعِهِ الشّعريّ ودراسة ذاتِه الإنسانيّةِ لأنّها بمنزلةِ المحرِّك والدَّافع لأيِّ إبداعٍ إنسانيٍّ ، وصِنوها في الحياةِ وهو الآخرُ وهنا يعمدُ البحثُ إلى فصلِ أبرزِ الملامحِ الذّاتيّةِ، عندَ شاعرٍ مشهورٍ كعمرَ ، الّذي شكَّلَ حالةً فريدةً في ساحةِ الإبداعِ الأدبيِّ الشّعريِّ، من خلالِ زعامتهِ شعراءِ الغزلِ في عصرهِ، وريادتهِ في الغزلِ الصَّريحِ ، وتجبُ الإشارةُ إلى أنَّنا نريد مصوّرةَ الآخرِ في شعرِ عمرَ بن أبي ربيعةَ في هذه الدِّراسةِ، صورةَ المرأةِ، وهذه الصّورةُ تقاربُ إلى حدٍّ كبير صورتَها لدى أكثر الشّعراء ، لكنَّها تتلوَّنُ في شعرِ عمرَ، لنجدَ العفيفةَ والعاشقةَ والمتمرِّدةَ المتفلِّتةَ من القيودِ. This study aims at analyzing the poetic content of the poetry of an Omayyad poet who was born to a wealthy family which was so close to the Court. The objective of the study is to shed light on one of the most salient features of literary creativity and literary masterpieces-whether poetic or prose- which is the human essence that stimulates human creativity and the doublet of this essence, that is the Other. This study attempts to identify the most prominent subjective features in the poetry of Omar as a famous poet who became a phenomenon in the field of poetic and literary creativity through mastering flirtation poets and poetry in his era. It should be mentioned that the image of the Other in Omar’s poetry examined in this study is the image of woman which considerably resembles that image presented in the work of the majority of other poets. However, this same image varies in Omar’s poetry. Woman is represented as the chaste, beloved, and the rebellious.